Functioning and support of small innovative enterprises affiliated with universities in Russia - Rustam A. Yalmaev, Luiza T. Eskerkhanova, Zulfiya K. Anaeva Laura Kh. Dzhabrailova,; Barzaeva, Madina A. (Opción, 2019)
The paper addresses the practical problems of development of small innovative enterprises at universities and analyzes the problems of state support of the small business. A new model of a strategic innovation partnership is described. The authors show the relation between the Russian economy modernization and the development of small innovative entrepreneurship. In conclusion, innovative activity is resource-intensive and requires expensive investments. The solution of the social and economic problems of small business, which commercializes the intellectual products of the university, must be entrusted to the state